TRANSFORMATIONAL LEADERSHIP IN THE EFFORTS OF INCREASING MOTIVATION, PERFORMANCE, AND JOB SATISFACTIONS AT PT BANK MANDIRI TBK - Marnis Atmojo (Universitas Hayam Wuruk Perbanas, 2012)
Transformational leadership is assumed to be influential in any company. It has some vitalrole in increasing motivation, performance, and job satisfaction. This study attempts to findout all the influences of transformational leadership in the company. The respondents areemployees of PT. Bank Mandiri Tbk at Pekanbaru, spreading to into eleven regional/branchoffices, with 102 middle managers. Interview and questioner were used with the measurementscale of 1-5. The study uses Structural Equation Model (SEM) and AMOS 17.0. It shows that:(1) Transformational leadership can provide significant influence and positive through employee’smotivation. (2) While transformational leadership influences insignificantly the employee’sperformance. (3) Employee’s motivation can provide and positive significant on employee’sperformance. (4) Employee’s performance has relationship with job satisfaction andhas significant and positive influence.